Development of Interactive Learning Multimedia Gate (Geometry of Space Building) to Increase Learning Motivation of Elementary School Students - Susanto, Mohammad Adi; Ifriqia, Fartika; Ratno, Puspoko Ponco (Proceeding International Conference on Education, 2023)
This research is motivated by the lack of utilization of learning media in mathematics subjects. The purpose of the research is to know the development, feasibility and influence of the use of interactive learning multimedia GERBANG (geometry build space) in increasing student learning motivation. The development research uses the APPED development model consisting of five systematic and logical stages, namely analysis, planning, production, evaluation, and dissemination. The results of the development research show that the interactive learning multimedia GERBANG (geometry builds space) gets a qualification assessment Very Feasible based on the validation of experts, namely media experts and material experts with the results of the percentage of feasibility of 87.5% by media experts and material experts of 85%. Based on the results of the user test at the pretest stage obtained an average value of 51, 32, while at the postest stage obtained an average value of 69.19. Thus, the use of interactive learning multimedia GERBANG (geometry build space) has an effect in increasing the motivation to learn.